GaN-Based Cyan Light-Emitting Diode with up to 1-GHz Bandwidth for High-Speed Transmission Over SI-POF - Juri Vinogradov; Roman Kruglov; Rainer Engelbrecht; Olaf Ziemann; Jinn-Kong Sheu; Kai-Lun Chi; Jhih-Min Wun; Jin-Wei Shi (IEEE Photonics Journal)
We demonstrate the performance of a novel cyan light-emitting diode (LED) on a patterned sapphire substrate for use as a light source for plastic optical fiber (POF) communications with the central wavelength at 500 nm. By significantly reducing the number of active InxGa1-xN/GaN multiple quantum wells and the thickness of the barrier layers down to 5 nm, such a device with an active diameter of 47 μm demonstrates a record high 3-dB electrical-to-optical bandwidth, as high as 1 and 0.7 GHz, among all the reported high-speed visible LEDs under room temperature and 110 °C operation, respectively. TO-Can packaging with a lens is used to enhance the POF coupling efficiency. Very-high data rates of 5.5 and 5.8 Gbit/s are achieved over step index POF under nonreturn-to-zero and 4-pulse amplitude modulation, respectively. When the POF transmission distance reaches 50 m, there is degradation in the maximum data rate for both modulation schemes to 1.3 Gbit/s due to the dispersion and attenuation of the POF.